Data Resource Profile: The Disability Statistics Questionnaire Review Database (DS-QR Database): A Database of Population Censuses and Household Surveys with Internationally Comparable Disability Questions - Carpenter, Bradley; Kamalakannan, Sureshkumar; Saikam, Pavani; Alvarez, David Vicente; Hanass-Hancock, Jill; Murthy, GVS; Pinilla-Roncancio, Monica; Rivas Velarde, Minerva; Teodoro, Douglas; Mitra, Sophie (International Journal of Population Data Science, 2024)
Introduction The 2030 Sustainable Development Agenda and the United Nations Convention on the Rights of Persons with Disabilities (CRPD) aspire to leave no one behind and call for the inclusion of persons with disabilities in all spheres of life. To monitor this goal of inclusion, CRPD's Article 31 requires state parties to collect data about the situation of persons with disabilities. The Disability Statistics – Questionnaire Review Database (DS-QR Database) reports on whether population and housing censuses and household surveys include internationally recommended disability questions for adults ages 15 and older. Methods The Disability Data Initiative (DDI), an international consortium of researchers, regularly retrieves and analyses a list of surveys and censuses from international catalogs, libraries and websites of national statistics offices. Questionnaires are reviewed to identify if they include internationally recommended questions on functional difficulties (e.g. difficulty seeing), more specifically (i) the Washington Group Short Set (WG-SS) or (ii) questions that meet at least the United Nations 2017 guidelines for disability measurement in censuses (other functional difficulty questions thereafter). Results The DS-QR Database includes the review results for the questionnaires of 3027 population censuses and surveys from 199 countries and territories collected from 2009 to 2023. The review has information on whether each dataset has the WG-SS or other functional difficulty questions and overall results per country, region, type of dataset and over time. Conclusion By identifying countries that collect internationally comparable disability data, the DS-QR Database can help researchers, policymakers and advocates determine whether countries fulfill their obligations as per CRPD Article 31. It can also assist in identifying which datasets use functional difficulty questions and can be used to research and monitor disability rights over time and across countries. The DS-QR Database is in a Supplementary file and will be accessible on a website upon publication of this article.